Clinical assessment of enamel wear caused by monolithic zirconia crowns - Stober, Thomas; Lorenzo Bermejo, Justo; Schwindling, Franz Sebastian; Schmitter, Marc (Journal of oral rehabilitation, 2016)
The purpose of this study was to measure enamel wear caused by antagonistic monolithic zirconia crowns and to compare this with enamel wear caused by contralateral natural antagonists. Twenty monolithic zirconia full molar crowns were placed in 20 patients. Patients with high activity of the masseter muscle at night (bruxism) were excluded. For analysis of wear, vinylpolysiloxane impressions were prepared after crown incorporation and at 6-, 12-, and 24-month follow-up. Wear of the occlusal contact areas of the crowns, of their natural antagonists, and of two contralateral natural antagonists (control teeth) was measured by use of plaster replicas and a 3D laser-scanning device. Differences of wear between the zirconia crown antagonists and the control teeth were investigated by means of two-sided paired Student's t-tests and linear regression analysis. After 2 years, mean vertical loss was 46 μm for enamel opposed to zirconia, 19-26 μm for contralateral control teeth and 14 μm for zirconia crowns. Maximum vertical loss was 151 μm for enamel opposed to zirconia, 75-115 μm for control teeth and 60 μm for zirconia crowns. Statistical analysis revealed significant differences between wear of enamel by zirconia-opposed teeth and by control teeth. Gender, which significantly affected wear, was identified as a possible confounder. Monolithic zirconia crowns generated more wear of opposed enamel than did natural teeth. Because of the greater wear caused by other dental ceramics, the use of monolithic zirconia crowns may be justified.